Poland’s Expectations in Connection with Multiannual Financial Framework (2014–2020) and Participation in the Process of its Development Exemplified by Selected Negotiation Phases (Economic and Political Thought, 2013)
One of the most important topics of 2011–2013 concerning the EuropeanUnion and its finances was the Multiannual Financial Framework 2014–2020.Its negotiations and the outcome will have a great influence on all the next7 years for all 28 countries of the Union and their citizens. The impact ofthe new MFF will be easy to recognize in the economic possibilities, in thestructure and issues of internal and external European policies. The mainconcern of this paper is an answer to a question regarding Polish expectationsin connection with the new budgetary framework as well as a closer look onthe involvement of our country in the long negotiation process. The firstpart of the article concerns the Polish national priorities in view of the MFF2014–2020, which are the cohesion policy and the Common Agricultural Policyfunds. They are described along with their current objectives, challengesand main beneficiaries. The Polish participation in the ongoing process of theMFF adoption is the main subject of the second part of the paper. The Polishgovernment, the opposition, Polish Euro-parliamentarians and employees ofother European institutions as well as the Polish society – all exert certaininfluence on the final outcome of the MFF 2014–2020.